Sovereign Mobile Mesh Networks - Venkata Santhi, N; Kumar, D (International Journal of Computer Sciences and Engineering, 2025)
Networks composed of mobile nodes inherently suffer from intermittentconnections and high delays. Performance can be improved byadding supporting infrastructure, including base stations, meshes,and relays, but the cost-performance trade-offs of different designsis poorly understood. To examine these trade-offs, we have deployeda large-scale vehicular network and three infrastructure enhancementalternatives.Mobile ad-hoc networks(MANETs) are ideal for situations where a fixed infrastructure isunavailable or infeasible. Today’s MANETs, however, may suffer from network partitioning. This limitation makes MANETs unsuitable for applications such as crisis management and battlefield communications, in which team members might need to work in groups scattered in the application terrain.In such applications, inter-group communication is crucial to the team collaboration. To address this weakness, we introduce in this paper a new class of ad-hoc network called Autonomous Mobile Mesh Network (AMMNET). We propose a distributed client tracking solution to deal with the dynamic nature of client mobility, and present techniques for dynamic topology adaptation in accordance with the mobility pattern of the clients. Our simulation results indicate that AMMNET is robust against network partitioning and capable of providing high relay throughput for the mobile clients.